Can radiant floor heating systems be used in removable glazed enclosed patios meeting thermal comfort standards?. (September 2016) - Astiaso Garcia, Davide
Abstract: Many systems are used for heating glazed enclosed patios of restaurants, pubs or other restaurant businesses. This paper explores the possibilities of use radiant floor heating systems (RFHS) in removable glazed enclosed patios maintaining thermal comfort in terms of predicted percentage of dissatisfied (PPD) and predicted mean vote (PMV) optimal ranges. The effects of different envelope structures of glazed enclosed patios on floor surface temperature using a radiant floor heating system have been analyzed. In addition, considering the use of removable and modular radiant floor heating panels, delivery and return pipes layouts from a heat power generator to each single radiant floor heating panel have been analyzed assessing flow velocity and pressure drops in order to pinpoint the best layout for optimizing heat transfer efficiency and energy saving. The findings showed at assumed outdoor and indoor temperatures what are the considered glazed enclosed patio envelopes that allow the use of a RFHS maintaining the floor surface temperature within thermal comfort ranges and avoiding local thermal discomfort due to floor temperature and vertical radiation asymmetry. Moreover, the flow velocity and concentrated/distributed pressure drops analysis pinpointed optimal pipe layouts for connecting heat power generator to each underfloor heating panel. concluding, the paper highlighted that, up to meet thermal comfort standards, under floor heating systems could be used for heating glazed enclosed patios only for certain envelope structures. Additionally, a delivery and return pipe layout should be properly designed for minimizing pressure drops and optimize heat transfer efficiency. Highlights: Underfloor heating system design in glazed enclosed patio is investigated. Effects of heat losses on floor surface temperature are assessed. Effects of pipes layout on thermal performance are considered. 4 glazed enclosed patio envelopes and 10 pipes layouts are modelled in detail. Results provide recommendation for selecting envelope structures and pipes layouts.